A The effect of work motivation and transformational leadership style on employee performance through organizational citizenship behavior as an internvening variable on BMT UGT Sidogiri Jember employees - Oktaviani, Lusi; Titisari, Purnamie; Suroso, Imam (International Journal of Scientific Research and Management (IJSRM), 2020)
The study aims to analyse and discuss work motivation variables and transformational leadership styles on employee performance, work motivation variables and transformational leadership styles in Organizational Citizenship Behaviour (OCB), and Organizatinal Citizenship Behaviour (OCB) variables on employee performance. The population in this study were all employees of BMT UGT SIDOGIRI Jember consisting of 152 people. The sampling method uses a sampling probability with a random sampling approach using the Sovlin formula so that a sample of 110 respondents is obtained. The research uses line analysis and SPSS 20.0 as an analytical tool. The results of this study are (1) The motivation of work is significant impact on Organizational Citizenship Behaviour of BMT UGT Sidogiri Jember Employees, (2) Transformational leadership style significant influence on Organizational Citizenship Behaviour on employees of BMT UGT Sidogiri Jember, (3) Work motivation is significant effect on the performance of BMT UGT Sidogiri Jember Employees, (4) The Transformational leadership style is significant to the performance of the employees of BMT UGT Sidogiri Jember , (5) Organizational Citizenship Behaviour has a significant effect on the performance of employees of BMT UGT Sidogiri Jember, (6) The motivation of work has a significant impact on performance through the Organizational Citizenship Behaviour on employees of BMT UGT Sidogiri Jember, (6) The Transformational leadership style is significant to the performance through the Organizational Citizenship Behaviour at BMT UGT Sidogiri